2020
DOI: 10.1111/vde.12841
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Bruton's Tyrosine Kinase Inhibitor (PRN‐473) in the treatment of canine pemphigus foliaceus

Abstract: BackgroundBruton's tyrosine kinase (BTK) is important in B‐cell signalling. Efficacy has been reported for BTK inhibitors (BTKi) in human autoimmune diseases. Canine pemphigus foliaceus (cPF) is the most common canine autoimmune skin disease.ObjectivesTo determine the safety and efficacy of a BTKi in cPF treatment.AnimalsNine privately owned dogs.Methods and materialsNine dogs diagnosed with PF were administered BTKi PRN473. Initial dosages were ≈15 mg/kg once daily, increased to twice daily if inadequate resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(49 citation statements)
references
References 37 publications
0
41
0
Order By: Relevance
“…4,5 Previous reports using BTKi in the treatment of cPF have included two posters, one of which presented findings of Dog 1 in the present study, 6 and our previous report on BTKi PRN473. 7 PRN1008 is an oral, reversible covalent BTKi developed by Principia Biopharma for the treatment of human autoimmune disease including pemphigus foliaceus; it has been given the generic name rilzabrutinib. 5,8 PRN1008 has undergone toxicological testing in healthy beagle dogs, including a 12 week Good Laboratory Practice study by Principia Biopharma.…”
Section: Btkmentioning
confidence: 99%
See 4 more Smart Citations
“…4,5 Previous reports using BTKi in the treatment of cPF have included two posters, one of which presented findings of Dog 1 in the present study, 6 and our previous report on BTKi PRN473. 7 PRN1008 is an oral, reversible covalent BTKi developed by Principia Biopharma for the treatment of human autoimmune disease including pemphigus foliaceus; it has been given the generic name rilzabrutinib. 5,8 PRN1008 has undergone toxicological testing in healthy beagle dogs, including a 12 week Good Laboratory Practice study by Principia Biopharma.…”
Section: Btkmentioning
confidence: 99%
“…The BTK probe PRN933 and BTK detection antibody (Clone 53, BD Biosciences; San Jose, CA, USA) used in this study were used as reported in a similar study of cPF and PRN473. 7 PRN933 was synthesized in-house and validated to show similar binding affinity to those studies. Further details of processing of the dogs' B cells and measuring BTK occupancy [% of the BTK enzyme in peripheral blood mononuclear cells (PBMC) bound by PRN1008] were as described previously.…”
Section: Laboratory Proceduresmentioning
confidence: 99%
See 3 more Smart Citations